2011
DOI: 10.1089/aid.2010.0345
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia, Hypochloremia, and Hypoalbuminemia Predict an Increased Risk of Mortality During the First Year of Antiretroviral Therapy Among HIV-Infected Zambian and Kenyan Women

Abstract: Early mortality rates after initiating antiretroviral therapy (ART) are high in sub-Saharan Africa. We examined whether serum chemistries at ART initiation predicted mortality among HIV-infected women. From May 2005 to January 2007, we enrolled women initiating ART in a prospective cohort study in Zambia and Kenya. We used Cox proportional hazards models to identify risk factors associated with mortality. Among 661 HIV-infected women, 53 (8%) died during the first year of ART, and tuberculosis was the most com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
26
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 29 publications
7
26
0
1
Order By: Relevance
“…We found that HIV patients with hyponatremia and who were at WHO clinical stage 4 had higher short-term mortality rates, which was similar to findings from previous studies (5,13,14). Hyponatremia is a common abnormality among HIV-infected adults with advanced HIV disease (15), and it was present in 28.4% of the hospitalized HIV patients in our study.…”
Section: Discussionsupporting
confidence: 91%
“…We found that HIV patients with hyponatremia and who were at WHO clinical stage 4 had higher short-term mortality rates, which was similar to findings from previous studies (5,13,14). Hyponatremia is a common abnormality among HIV-infected adults with advanced HIV disease (15), and it was present in 28.4% of the hospitalized HIV patients in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Dao et al . reported research indicating high mortality in the first year of initiating HAART in a population of African female patients with both hyponatremia and hypochloremia [14]. However, a number of issues remain to be clarified, such as whether hyponatremia independently influences the long-term survival of HIV/AIDS patients, the effect of serum sodium concentration on patient mortality, the relationship between serum sodium concentration, CD4+ cell counts, the severity of HIV/AIDS and the impact of hyponatremia on patient survival in other populations.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies by Dao et al . indicated that a serum sodium concentration below 135 mmol/L combined with hypochloremia lead to a high first year mortality in female AIDS patients [14]. However, further investigations are required to elucidate the relationships between serum sodium concentrations and CD4+ cell counts, WHO stages and HIV-RNA levels, and whether hyponatremia is an independent risk factor for death in HIV/AIDS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have examined the associations of serum albumin with adverse events in HIV-infected individuals 89101516 . However, no previous studies, to our knowledge, have evaluated the relationship between serum albumin and longitudinal kidney function in an HIV-infected population, and few have studied serum albumin and kidney disease in the general population 1117 .…”
Section: Discussionmentioning
confidence: 99%